Realistic mathematics education on arithmetic sequences and series material by calculating chair rows - Elvindi Gestikatama; Yuha Nissa Prasasti; Angelina Dwi Susanti; Dewi Hamidah (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This research was conducted at MTs Sunan Muria Ploso with the aim of describing the application of realistic mathematics education material of row and arithmetic series. Some research said that, in schools, applies mathematical concepts directly which causes students to feel bored quickly and the methods used are less varied. In order for mathematics learning to be creative, interesting and fun, then one way is to apply the Realistic Mathematics Learning approach. This research is a descriptive qualitative research with 40 students of class VIII-D MTs Sunan Muria Ploso as the subjects. Data collection techniques using the method of documentation, and interviews conducted by researchers with students. Data collection techniques using the method of documentation and interviews conducted by researchers with students. The sampling technique used was purposive sampling. The data analysis technique in this research is qualitative data analysis, which consists of data reduction, data presentation, and drawing conclusions. The research instrument is a test and interview guide. The results showed that the arithmetic series material can be applied well with the RME approach. The conclusion of this study is that the Learning with Realistic Mathematics approach can support students in understanding and determining arithmetic series formulas, students use various symbols in implementing them so as to help students understand the concepts of arithmetic series.